Descriptive Study of The Risk of Mental Health Disorders in Midwives at The Putra Medika Group Cikarang Clinic in 2022 - Maya, Silvia; Azteria, Veza; Sangadji, Namira Wadjir; Yusvita, Fierdania (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Mental health problems that occur in medical and health workers not only affect the quality of service and decision-making capacity which can hinder health service efforts, but have a lasting effect on their overall well-being.  Objective: The purpose of this study was to describe the risk of mental health disorders in midwives at Putra Medika Group Cikarang Clinic in 2022. Method: This type of quantitative research is descriptive in nature, the research sample was all midwives at Putra Medika Group Clinic totaling 37 midwives, Result and Discussion: The results showed that of the 37 midwives, more than half of the sample, namely 30 midwives (81.1%) had normal stress. The results of anxiety showed that 14 midwives (37.8%) had normal anxiety, 10 midwives (27.0%) had severe anxiety. Conclusion: More than half of the sample, namely 30 midwives (81.1%), had depression in the normal category. As for the characteristics of the respondents, they included: 37 midwives (100%) aged <35 years, 29 midwives (78.4%) were single, and 34 midwives (91.9%) had a working period of <5 years